Terrestrial Liming As a Restoration Technique for Acidified Forest Ecosystems - Sarah E. Pabian; Shawn M. Rummel; William E. Sharpe; Margaret C. Brittingham (International Journal of Forestry Research)
We studied the effects of liming on soils and forest songbirds as well as vegetation and calcium-rich invertebrate prey variables that were predicted to link birds to changes in soil conditions. We observed increases in soil pH, calcium, and magnesium, as well as in songbird abundances in response to lime application, with continuing increases through five years after liming. We observed an overall increase in snail abundance on limed sites, but an initial peak of a 23 fold increase three years after liming was reduced to an 11 fold increase five years after liming. We observed an increase in forb ground cover on limed sites, but liming had no effect on millipede abundance or other vegetation measures. Of the variables we measured, snail abundance was the most likely mechanism for the response in bird abundances. Because we observed continued benefits of liming up to five years post treatment, we concluded that liming is a very promising technique for restoring forest ecosystems impacted by acidic deposition.